Doubly charged Higgs through photon-photon collisions in 3-3-1 models - Cieza Montalvo, J. E.; Cortez, Nelson V.; Tonasse, M. D. [UNESP] (Amer Physical Soc, 2008)
We study the production and signatures of doubly charged Higgs bosons (DCHBs) in the process gamma gamma <-> H(--)H(++) at the e(-)e(+) International Linear Collider and CERN Linear Collider, where the intermediate photons are given by the Weizsacker-Willians and laser backscattering distributions.